Earthquakes of the Indian Subcontinent Seismotectonic Perspectives - Rajendran, C. P.; Rajendran, Kusala (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book highlights some of the interesting recent and historical earthquakes (1803 Uttarkashi, 1819 Kutch, 1897 Shillong, 1905 Kangra, 1934 Nepal-Bihar, 1950 Upper Assam, 1967 Koyna, 1993 Killari, 1997 Jabalpur, 2001 Bhuj, 2004 Sumatra-Andaman, 2005 Kashmir, and 2015 Nepal) that occurred in India and in the vicinity. The tectonic and geodynamic significance of the modern (after the advent of global network) earthquakes in relation to some of the historical earthquakes like the 1819 Kachchh and 1897 Shillong and 1934 Nepal-Bihar earthquakes in the light of newer understanding is discussed. It also contains detailed expositions of seismotectonics and mechanisms of each earthquake. It concludes with touching upon future earthquake hazard scenario in India in view of the present and past earthquakes.
Introduction -- Seismological concepts and global seismological research -- Uttarkashi, 1803 -- Kachchh, 1819 -- Shillong, 1897 -- Kangra, 1905 -- Nepal-Bihar, 1934 -- Upper Assam, 1950 -- Koyna, 1967 -- Killari, 1993 -- Jabalpur, 1997 -- Bhuj, 2001 -- Sumatra-Andaman, 2004 -- Kashmir, 2005 -- Nepal, 2015 -- Future Hazard Scenario.
Keywords: Geology; Earth sciences; Natural disasters; Geology; Earth Sciences; Natural Hazards; Earth Sciences